Assessment On Flow Characteristics Of Tawau’s Spillway Hydraulic Physical Model - Munusamy, Shanbagarani (Universiti Sains Malaysia, 2019)
The spillway is among the most important structures of a dam project. It provides the project with the ability to release excess or flood water in a controlled or uncontrolled manner to ensure the safety of the project. It is of paramount importance for the spillway facilities to be designed with sufficient capacity to avoid overtopping of the dam, especially when an earthfill or rockfill type of dam is selected for the project. High velocity results in low or negative pressure on the spillway slab, scouring and erosion at downstream area. Whereas, negative pressure leads to cavitation and may cause critical damage on spillway structure. This study aims to investigate the flow characteristics along spillway such as water depth, velocity, pressure and energy dissipation on the stilling basin. Tawau Dam’s Spillway is a 1:30 scaled spillway physical model was constructed and assembled in Hydraulic Laboratory of Universiti Sains Malaysia. This study has been conducted on two different flow rate (196 m3 /s, and 392 m3/s) with total of 109 measurement points for each case.To ensure the release flow is safe from causing severe damage on the downstream area, the study was focused on stilling basin as well. Based on the results, hydraulic jump length ,depth and velocity thecurrent Type II stiling basin suitable to used. Lastly, the Case 2 has been recommended to use Type III Stilling Basin for long period assessment. Thus, it can be concluded that the Type II Stilling Basin is suitable for both Case 1 and Case 2.